Cosmetic Reconstruction of Frontotemporal Depression Using Polyethylene Implant after Pterional Craniotomy. - Im, Sang Hyuk; Song, Jongkeun; Park, Sang Kyu; Rha, Eun Young; Han, Young-Min (BioMed Research International, 2018)
Purpose. Pterional craniotomy is a useful approach for the treatment of a variety of intracranial pathologies. However, it can result in temporal hollowing, which causes significant craniomaxillofacial asymmetry and esthetic deformity. The present study was performed to determine the postoperative outcomes of patients following frontotemporal depression reconstruction using a high-density porous polyethylene (HDPE) implant (Medpor®; Stryker, Kalamazoo, MI) after pterional craniotomy. Materials and Methods. The patients had undergone reconstruction of frontotemporal depression using Medpor® implants after pterional craniotomy at our medical institution during the period from February 2010 to March 2014. We evaluated the thickness and volume of both the temporalis muscle and Medpor® implant through a retrospective review of the medical records and computed tomography (CT) scans of 92 patients. Results. The mean temporalis muscle thickness ratio (muscle thickness of the affected side/nonaffected side) was 0.61 ± 0.16. The mean reconstructed temporalis muscle thickness ratio (muscle and Medpor® implant thickness of affected side/muscle thickness of nonaffected side) was 1.15 ± 0.02. The mean temporalis muscle volume ratio (muscle volume of affected side/nonaffected side) was 0.67 ± 0.02. The mean reconstructed temporalis muscle volume ratio (muscle and Medpor® implant volume of affected side/muscle volume of nonaffected side) was 1.18 ± 0.02. Conclusions. Temporalis muscle thickness and volume were significantly decreased on the affected side after pterional craniotomy. Reconstruction of frontotemporal lesions using Medpor® implants after the pterional approach improved temporal hollowing without additional complications.